Avaliação psicomotora de crianças com distúrbios respiratórios do sono - Ferreira, Vanessa Ruotolo [UNIFESP] (2019)
Objective. To evaluate psychomotor performance in children with Sleep Disordered Breathing. Method. It was a cross-sectional study, carried out with children aged 7-11 divided into 3 groups: OSAS (Obstructive Sleep Apnea Syndrome), Primary Snoring (PS) and Control Group (CG-No Sleep Disorders). They were evaluated with Polysomnography and Motor Development Scale (MDS). Results. OSAS group presented a worse score in global motricity when compared to the PS group (p=0.045). PS group had worse performance in balance when compared to CG (p=0.037). OSAS group presented a worse performance in relation to other groups (p=0.002) in body scheme/speed. PS group presented worse performance in EDM´s classification when compared to CG (p=0.053). Conclusion. Global motricity and Body scheme/speed were impaired in children with OSAS. Balance was impaired in children with PS.